2022
DOI: 10.1177/23259671221097438
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ankle Injury on Subsequent Ankle, Knee, and Shoulder Injuries in Competitive Badminton Players Younger Than 13 Years

Abstract: Background: In recent years, there has been a trend in badminton toward more specialized training at an earlier age. Accompanying this trend is the increased frequency of injuries in young players. Ankle injury is the most common injury in pediatric sports; however, its influence on subsequent injuries is rarely considered. Purposes: To evaluate the incidence of ankle, knee, and shoulder injuries in youth badminton and to investigate the influence of ankle injuries on subsequent ankle, knee, and shoulder injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…For random-light reaction time, the results revealed a shorter reaction time for the forehand side than for the backhand side. The players moved by shifting their center of gravity after receiving stimulating information; this principle conforms with the theory of perception and decision-making in agility [ 2 , 18 , 19 ], indicating a crucial association between agility and specific athletic performance. Similarly, the results of the present study revealed significant improvements in the reaction time performance of its participants.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…For random-light reaction time, the results revealed a shorter reaction time for the forehand side than for the backhand side. The players moved by shifting their center of gravity after receiving stimulating information; this principle conforms with the theory of perception and decision-making in agility [ 2 , 18 , 19 ], indicating a crucial association between agility and specific athletic performance. Similarly, the results of the present study revealed significant improvements in the reaction time performance of its participants.…”
Section: Discussionsupporting
confidence: 72%
“…Lower limb joint loading affects the athletic performance of badminton players. Studies have revealed that incorrect footwork movements have a negative effect on the state of lower limb joints and cause injuries [ 19 , 20 , 21 ]. For inappropriate footwork movements involving lunges, the body compensates by shifting the trunk inclination angle of the lower limb joints, which in turn affects the efficiency of shots and causes injuries [ 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the information about training volume in adolescent badminton players is scarce. Only a few studies are available and researchers reported weekly training volumes ranging between 16-20 h hours at ages below 13 years old, with training volume increases up to 25 h per week in competitive players aged 13-15 years [25,26]. Our results showed that the analyzed sample is far from this training volume, which highlights the recreational character of our study sample.…”
Section: Discussionmentioning
confidence: 60%